SAT0203 Significance of extension of tocilizumab infusion intervals from 4 weeks to 6 weeks in ra patients who had shown good response to 4 week intervals. (15th June 2017) - Uda, H; Shigematsu, K; Saiki, O
Abstract : Background: A period of 4 weeks (w) has been recommended as tocilizumab (TCZ, 8mg/kg) infusions. However, we found that 5 or 6w intervals were also effective in more than 90% of RA patients with low disease activity (LDA) at 4w intervals (1). Objectives: We conducted the study to investigate the significance of extension of intervals from 4w to 6w. We compared, in the same patients, the clinical features such as diseases activity, major and minor side reactions between at 4w and at 6w. Moreover, we also considered the mechanisms. Methods: This was a retrospective observational study. Among RA patients who had shown LDA with TCZ infusions at 4w intervals, the patients who could extend the intervals from 4w to 6w with LDA for more than 2 years without changing the doses of oral medicines were enrolled. In the same patients, we compared the events of serious and common side reactions between at 4w and 6w intervals. We examined the course of the levels of total cholesterol (TCHO), triglyceride (TG), and platelet (PLT) counts. We also examined the levels of serum trough TCZ and IL-6. Results: Among 120 patients who maintained LDA at 4w intervals, more than 60% of patients maintained LDA at 6w intervals. When we compared the disease activity of 6w-responders between at 4w and 6w-intervals, all parameters reflecting the disease activities such as CRP and DAS28CRP score at 6w intervals were elevated significantly, but were still within LDA. At 4w intervals, serious adverse events were occurred as much as 11 cases during 2 years. At 6w intervals, however, they were decreased to 3 cases only in the same period. The common adverse events such as general fatigue, nausea, and dizziness occurred frequently at 4w intervals in most of the patients. At 6w intervals, these common adverse events were decreased significantly. At 4w intervals, the levels of TCHO and TG were elevated significantly. At 5w and 6w intervals, however, they were decreased accordingly. At 6w intervals, they were within normal limits. In most of patients, the levels of PLT counts were decreased significantly at 4w intervals. At 5w and 6w intervals, however, they were increased gradually. When TCZ were infused at 4w intervals, the serum trough TCZ levels were around 10 μg/mL. In contrast, they became undetectable when extended to 5w, and it is obvious that the trough TCZ levels of 6w were lower than 5w. The levels of IL-6 were significantly high at 4w-intervals, but the levels of IL-6 were decreased to less than 10 pg/mL at 5w-intervals. Conclusions: The present study provide evidence that more than half of RA patients who showed good response to TCZ infusions at 4w could extend the intervals to 6w. By extension of intervals to 6w, major and minor side reactions were reduced significantly, and the levels of TG, TCHO and PLT were also normalized with sustaining LDA, suggesting that the dose of TCZ (8mg/kg) at 4w intervals might be excessive in some patients. Taken together, we should be careful for deciding the intervals of TCZ infusion in each patient. References: Saiki O, Uda H. Successful extension of tocilizumab infusion intervals from 4 weeks to 6 or 5 weeks in 90% of RA patients with good response to 4 weeks intervals. Clin Exp Rheumatol (2017 in press). Disclosure of Interest: None declared